Magnetic oscillation spectrum of surface resistance in layered organic compounds - Krstovska, Danica; Skeparovski, Aleksandar (IOP Publishing, 2023)
Abstract The magnetic quantum oscillations of surface resistance in quasi-two dimensional layered organic conductors have been obtained numerically for a magnetic field parallel to the surface. The resonance fields, which were theoretically calculated in a previous work on surface states, are found to coincide closely to the positions of the maxima in the ∂R/∂B curves. We find that, in quasi-two dimensional organic conductors, the transitions between the adjacent surface states are the most present transitions in the sum curve for surface resistance derivative oscillation spectrum. Our results, obtained from the calculations of the oscillation spectra of the individual series and the sum of six series, confirm that the theoretical description of surface states in the anisotropic organic conductors is essentially correct in its numerical aspects. These studies will be very helpful for analyzing and explaining the experimental curves and for their comparison with the theoretical results. Since there are yet no experimental data on surface impedance oscillations in quasi-two dimensional organic conductors with this work we would like to shed new light on this problem in order to motive new research in that direction mostly because of a need of such studies for a possible utilization of surface effects in the existing organic devices.